Implementation of Anti-Bullying Education Values in Akidah Akhlak Subjects - Muhammad Ilham Syahputra; Syamsu Nahar; Fibri Rakhmawati (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to determine the values ​​of anti-bullying education in the Akidah Akhlak subject and its implementation, the obstacles faced in its application, and the positive impact after the learning is carried out. This research uses descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The findings in this study reveal that the values ​​of anti-bullying education in Akidah Akhlak subjects at SMPs Al-Azhar Medan are the values ​​of khauf, obedient, patient, kind, tolerant, helping, brave and communicative. Meanwhile, in its implementation, Akidah Akhlak teachers use interesting learning stages and varied methods such as the story method. The obstacles faced include internal and external factors. Meanwhile, after the implementation of anti-bullying education, the positive impacts were that there were no more reports from anti-bullying change agent students about students bullying their friends and the report notes were empty about students who were brought to the BK (Counseling Guidance) room about bullying problems.